1998
DOI: 10.1046/j.1469-8137.1998.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide‐concentrating mechanism and the development of extracellular carbonic anhydrase in the marine picoeukaryote Micromonas pusilla

Abstract: A range of marine photosynthetic picoeukaryote phytoplankton species grown in culture were screened for the presence of extracellular carbonic anhydrase (CA ext ), a key enzyme in inorganic carbon acquisition under carbonlimiting conditions in some larger marine phytoplankton species. Of the species tested, extracellular carbonic anhydrase was detected only in Micromonas pusilla Butcher. The rapid, light-dependent development of CA ext when cells were transferred from carbon-replete to carbon-limiting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…1b), whereas extracellular activity increased as a means of uptaking the bicarbonate ion, which became the major source of inorganic carbon as a result of alkalization. Similar profiles of extracellular CA activity along ten days of laboratory cultivation were observed for the microalgae Micromonas pusilla and Prorocentrum minimum (15,23,24).…”
Section: Discussionsupporting
confidence: 55%
“…1b), whereas extracellular activity increased as a means of uptaking the bicarbonate ion, which became the major source of inorganic carbon as a result of alkalization. Similar profiles of extracellular CA activity along ten days of laboratory cultivation were observed for the microalgae Micromonas pusilla and Prorocentrum minimum (15,23,24).…”
Section: Discussionsupporting
confidence: 55%
“…In the current study, however, there was no observed increase in POC production (Fig. 2) under higher pCO 2 levels, which could 305 be expected assuming lowered costs due to CCM down-regulation (Iglesias-Rodriguez et al, 1998;Rost et al, 2008). The observed increase in growth rates nonetheless indicates beneficial OA effects, potentially due to re-allocation of energy liberated by eased carbon acquisition.…”
Section: Picoeukaryotes Benefit From Ocean Acidification Irrespectivecontrasting
confidence: 49%
“…CCMs were described for even tiny picoeukaryotic marine phytoplankton (<2 μm) in which the diffusion of CO 2 is not expected to limit photosynthesis (Iglesias-Rodriguez et al 1998, Giordano et al 2005. A critical finding in this research was that phytoplankton leak substantial CO 2 and DIC to seawater in a light-dependent manner (Tchernov et al 1998(Tchernov et al , 2003, confirming that the operation of CCMs concentrates DIC inside cells in excess of seawater concentrations and that CCM activity is an active, energy-consuming process.…”
Section: Ccms In Marine Phytoplanktonmentioning
confidence: 53%